Anthropometrical and physiological profiles of the Algerian Olympic judoists - Almansba, R.; Sterkowicz, S.; Belkacem, R.; Sterkowicz-Przybycien, K.; Mahdad, D. (Archives of Budo, 2010)
Background and study aims: to establish the anthropometrical and physiological characteristics of male and female of the Algerian Olympic judo team. Material and methods: Thirteen members of the Algerian judo team, seven males aged 27.14 ± 3.02 years and six females aged of 24 ± 4.14 years. The anthropometrical dimensions were carried out: body weight, 6 height point, 6 breadths, 5 circumferences and 4 skinfold thickness. Body fat was estimated using Durnin and Womersley method. The body composition (BC) Hattori chart was used for the representation of individual percentage fat (PF %), (FFMI), (FMI) (BMI). For physiological tests, were used: Ruffier-Dickson test Power output (PWC170 cycle test). Results in jumping Sargeant test (VJ) was also used for counting power (P) according to Lewis formula. Results: A sexual dimorphism observed on the morphological variables. Males are higher in two lengths (anterior iliac spine and Acromion-dactylion III points), three breadths (thorax transverse, knee and elbow), and 3 circumferences (thorax, relaxed arm and waist) than females. A significant differences (p<0.05) exists between males and females in body composition (BM, PF%, FFM, FFMI) and RDI. However we didn`t observe a sexual dimorphism in: height and BMI, PWC170 and O2max, VJ and Power. Conclusion: We must have consider the both components FFMI and FMI to interpret the BMI . The new rules of IJF requires 5 minutes duration in female combat and the golden score proposal in case of combat tie. Thus, it is imperative to increase their O2max for a better performance optimization.